(untitled) (International Journal of Built Environment and Sustainability, 2023)
The dearth of land in high-density urban centres necessitates constructing structures with deep interiors, with little or no connection to the external environment. Additionally, the negative relationships between high-rise structures in the city centres in recent times are increasingly making contact with the outdoor environments undesirable. Whether in the built environment, decision sciences, healthcare, or technological disciplines, there is a need to understand the factors necessary for windowless office implementation, its prominent researchers, and geographical contexts, among other conditions for practical application. These background variables could assist in arriving at emerging themes, problems and gaps for concrete windowless office development in Malaysia. In this systematic review, the bibliographic information of title, abstract and keywords was mined from 255 documents on the Scopus database to generate scientometric maps and links showing relationships on co-authorship, co-citation, co-occurrences, and bibliometric coupling. The top trending variables in windowless office research are COVID-19, energy efficiency, indoor air quality, heart rate variability, performance assessment, visual reality, and workplace environment. Like other advanced economies in Asia, Malaysia is seen to attain a satisfactory level of development to implement the windowless office design module, with stable electricity power, technological advancement, and psychological stability of the people. The emerging variables in this review will give novel directions in exploring the developmental, psychological and health conditions for effective windowless office implementation in the country and similar economies in Asia, Africa and South America, where metropolises are fast becoming compacted due to ever-growing city centres